Higher establishment of nonnative trees with increased harvest intensity in strip cuttings - Dimarco, Romina Daniela; Nacif, Marcos E.; Garibaldi, Lucas Alejandro; Nuñez, Martin Andrés (New Forests, 2024)
Proper management of woody ecosystems is fundamental for human livelihoods and biodiversity conservation. Strip cutting or selective harvesting are proposed as sustainable alternatives to clear-cut logging. However, their impacts are not fully understood, especially when we consider the harvesting intensity levels and the invasibility of an ecosystem by nonnative tree species. In this study we analyzed the impacts of different harvesting intensity levels on the establishment after 2 years of nonnative and native tree species. We conducted this study in a mixed forest dominated by Nothofagus antarctica, where we applied four strip harvesting levels: 0% (control), 30%, 50% and 70% percentage of vegetation removal in eight plots (1417.5 m2 each plot) Inside those plots, we had a total of 24 subplots (3 sites × 8 plots) were we sowed seeds of a total of six tree species, that can form dominant stands in the studied region. Three species were nonnative invasives in the region (Pinus ponderosa, Pinus contorta and Pseudotsuga mensiezii), and the other three were native species (Austrocedrus chilensis, Nothofagus obliqua and Araucaria araucana). We found that in the high harvesting intensity treatments, the establishment after 2 years of all nonnative trees and only one native species (A. araucana) was increased in spite of the ecological and structural differences (i.e., productivity levels) between sites. Invasion by nonnative tree species can have important negative economic and ecological consequences on the logged ecosystems, so their removal may be required to keep them away from colonizing and dominating the logged areas, especially at high harvesting intensities. EEA Bariloche Fil: Dimarco, Romina D. University of Houston. Department of Biology and Biochemistry; Estados Unidos Fil: Dimarco, Romina Daniela. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Bariloche. Instituto de Investigaciones Forestales y Agropecuarias Bariloche. Grupo de Ecología de Poblaciones de ...